Therapeutic strategies in cancer biology and pathology - Sherbet, G. V. (Gajanan V.) (Amsterdam Elsevier, 2013)
Currently, intensive effort is being directed toward the identification of molecular targets that can provide approaches to the development of novel therapeutic strategies in cancer management. This book focuses on metastasis-associated genes, metastasis promoter and suppressor genes, which relate specifically to behavioral alterations of cancer cells in epithelial mesenchymal transition, cancer stem cell maintenance and propagation, and to the acquisition of invasive and metastasis faculty. The function of these genes has implications for cell cycle regulation and cell proliferation and so constitute an essential element in cancer growth and dissemination.
The Canonical and Non-canonical Wnt Routes of SignallingFzd and LRP Inhibition, Dkk and SFRPs; Fzd and DVL Interaction; 7 Therapeutic Targeting of TGF-[beta] Signalling; Antisense Oligonucleotide Trabedersen (AP 12009); Anti-TGF-[beta] Monoclonal Antibodies; Lerdelimumab, Metelimumab and Fresolimumab; Small Molecule Inhibitors of the TGF-[beta] Receptor Family; Inhibition of Type RIII Function; 8 EGFR Signalling in EMT; E-cadherin in EGFR Signalling; EGFR Signalling Path to EMT; ECM and Cell Membrane Components in EGFR Signalling; EGFR and TGF-[beta] Signalling Pathways Interact in EMT.
Includes bibliographical references.
Keywords: Cancer -- Genetic aspects; Cancer -- Molecular aspects; Cancer -- Treatment; Neoplasms -- genetics; Neoplasms -- therapy; Genetic Therapy -- methods; Electronic books